Polyphenol metabolites in fermented foods: biotransformation, bioavailability, and functional roles - Alharbi, Nouf Abdullah (Frontiers in Nutrition, 2026)
Polyphenols, plant-derived bioactive compounds, are known for their antioxidant, anti-inflammatory, and antimicrobial properties, benefiting plant-based foods. Fermentation, driven by microbial enzymes like glycosidases, esterases, and decarboxylases, alters the chemical structure of polyphenols, enhancing their bioavailability and bioactivity. This review explores the transformation of polyphenols, particularly flavonoids and phenolic acids, during fermentation, resulting in bioactive metabolites with increased solubility, stability, and antioxidant activity, improving gastrointestinal absorption. Additionally, fermented polyphenol metabolites modulate gut microbiota by promoting beneficial bacteria such as Lactobacillus and Bifidobacterium, while inhibiting pathogens. These changes support gut health, reduce inflammation, and provide systemic benefits, including enhanced metabolic, immune, and neurocognitive functions. Despite progress, knowledge gaps remain, particularly regarding microbial pathways and the health outcomes linked to these metabolites. Future research should focus on mapping microbial biotransformation pathways of polyphenols and their impact on health outcomes. Additionally, well-controlled human intervention studies using multi-omics approaches are necessary to validate the systemic benefits of fermented polyphenol metabolites.